Devices containing allyl isothiocyanate against the growth of spoilage and mycotoxigenic fungi in mozzarella cheese. Issue 11 (19th October 2018) - Tracz, B. L.; Bordin, K.; Bocate, K. C. P.; Hara, R. V.; Luz, C.; Macedo, R. E. F.; Meca, G.; Luciano, F. B.
Abstract: Filter paper and stickers containing allyl isothiocyanate (AIT), as well as pouches containing mustard meal and water for intrinsic production of AIT, were tested against aflatoxigenic strains of Penicillium digitatum CECT 2954 and Aspergillus parasiticus CECT 2681 in sliced mozzarella. Slices were inoculated with either fungus, packaged in plastic bags or plastic trays with one antimicrobial device (2–16 µL/L of AIT). Control groups presented visual growth of P. digitatum after 19.0 ± 1.5 d in bags and 26.1 ± 2.1 d in trays. A. parasiticus was visually detectable after 41.4 ± 1.7 d and 28.4 ± 1.5 d in trays and bags, respectively. AIT‐treated samples did not present visual fungal growth for 60 d. In trays, aflatoxin B1 was present only in the control; and in plastic bags it was found in the control (6.03 ± 1.23 mg/kg) and in groups treated with 2‐µL/L AIT: filter 0.03 ± 0.05, sticker 0.56 ± 0.13 and pouches 2.02 ± 0.05 mg/kg. Results show that all devices could increase the shelf life and safety of mozzarella. Practical applications: AIT is a component of brown/black mustard essential oil with antimicrobial activity. This natural substance was used in a newly designed bioactive packaging system to inhibit fungal growth. The device was an effective alternative to inhibit the growth of P. digitatum and A. parasiticus in sliced mozzarella cheese packaged in plastic bags or plastic trays. The antimicrobial sticker could be easily applied in products that are sliced in supermarkets and specialized shops, as well as in the industry avoiding the use of synthetic preservatives, such as sorbates and propionates.